FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP RETURN SAHAM PADA SEKTOR INDUSTRI BARANG KONSUMSI - Ni Luh Gde Novitasari; Ni Luh Putu Sandrya Dewi; I Wayan Udi Prayoga (Universitas Triatma Mulya, 2023)
This study aims to determine and test the effect of Earning Per Share (EPS), Price Earning Ratio (PER), Price to Book Value (PBV), Debt to Equity Ratio (DER) and Dividend Yield (DY) on stock returns in manufacturing sector companies consumer goods industry listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The research population is manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample in this study were 63 manufacturing companies in the consumer goods industry sector which were determined based on the purposive sampling method. The analytical technique used in this research is multiple linear regression analysis. Based on the results of the study, it shows that Price Earning Ratio (PER) and Dividend Yield (DY) have a positive effect on stock returns, Debt to Equity Ratio (DER) has an effect negatively on stock returns, Earning Per Share (EPS) and Price to Book Value (PBV) have no effect on stock returns.